Personhood in Biblical and Patristic Thought: A Journey from Natural to Spiritual Man - Hendi, Hendi; Nagoya, Rocky; Harefa, Yaaro; Santosa, Monica; Angelina, Claudia; Sugianto, Sugianto (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
This research challenges the materialistic view of humanity by offering a biblical and orthodox anthropological counter-narrative. It posits that human existence transcends mere matter, encompassing the body, soul, and spirit created in God's image and destined for divine communion (theosis). By examining key New Testament terms, such as natural, carnal, and spiritual man, through the lens of Patristic thought, particularly Gregory Palamas and Philokalia, this study reveals a dynamic transformation process from the natural to the spiritual man. This contrasts with the reductionist approach to materialism, demonstrating the richness and depth of the biblical and Orthodox understanding of human nature. This study contributes to a more comprehensive understanding of human identity and purpose by bridging the gap between biblical theology and contemporary philosophy, offering a fresh perspective on the complex interplay between the physical, spiritual, and divine aspects of humanity.